Public engagement during full‐scale exercises: Dimensions of trust and community resilience. (2nd December 2021) - Humann, Michael; Collie, Craig; Bright, Kayte; Thomsen, Janne; Crook, Phil
Abstract: The aim of this exploratory study is to understand the potential benefits to and limitations of inclusion of members of the community in Full Scale Exercises (FSX) that simulate disaster responses, with particular emphasis on volunteer trust, confidence, and community resilience. As these events contribute to skill maintenance and development of responders, it is also important to understand what additional benefits they potentially present in terms of engagement with the public and local communities. Better recognition of this impact on trust and confidence aids organisers and planners, while also providing clearer utility of investment and resources. Pre‐ and postintervention surveys, including quantitative and qualitative elements, were given to volunteer role‐players who took part in an FSX. Sixty‐five completed the pre‐exercise survey and 24 completed the postexercise survey. An additional 126 responses were received for a casualty role‐player survey. Correlations were applied to the statistics while qualitative elements were examined using thematic analysis. Findings demonstrated that involvement in the FSX created opportunities for learning but that community faith in emergency services could be diminished if the purpose of the FSX is not clearly communicated. Overall reduced rates in volunteer confidence could be explained by gaining increased perspective into the complexities of disaster management. The implication is that FSXs can meaningfully enhance community learning, trust, and resilience but only if the community involvement is properly and holistically managed. This is among the first studies to take the opportunity to examine the learning outcomes for volunteers of an FSX. Recommendations and increased awareness of this impact are important for future organisers, to maximise the benefits of their exercises and ensure that planning takes into consideration this often‐overlooked component.